IMPLEMENTATION OF A HUMAN FIREWALL TO PREVENT SOCIAL ENGINEERING THREATS IN REALIZING CYBER SECURITY - Faidin, Firman; Rimbawa, H.A. Danang; Saputro, J.W. (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2025)
The rapid development of information and communication technology has provided many conveniences in various aspects of life. However, on the other hand, this also brings increasing cyber security threats, one of which is the threat of social engineering. Therefore, this research aims to analyze the implementation of a human firewall to prevent social engineering threats in realizing cyber security. The research method used is a qualitative research method with in-depth interviews with several key informants including cyber security managers, employees involved in training programs, and cyber security experts in PT. Mekar Armada Jaya Magelang. From the results of the research that has been carried out, it can be concluded that the implementation of a human firewall is effective in preventing social engineering threats and improving cyber security. The integration of enabling technology with human training strengthens the company's defenses, while clear security policies and top management support help overcome the challenges of participation and organizational culture change. However, challenges such as low employee participation and resistance to cultural change remain. For greater success, the training approach should be relevant to the employee's role, use technology to increase engagement, and involve employees in the development of training materials. The success and failure case studies found show that this strategy can be adapted and improved continuously.